QoS-aware routing in emerging heterogeneous wireless networks. - Kung Yan; Yumin Wu.; Hsiao-Hwa Chen.
The integration of different kinds of wireless mobile networks, or heterogeneous wireless networks (HWNs), is emerging. However, a systematic discussion with regard to the special requirements and the complexity of QoS-aware routing in such networks and how QoS is blended with routing is still largely missing. This article aims to cast some light on these aspects. Based on an analysis of the basic architecture of an emerging heterogeneous wireless network and its new requirements on QoS-aware routing, a policy-based QoS supporting system infrastructure and a QoS-aware routing algorithm called QRA are presented in this article. The presentation is specifically given to these issues and components that are unique to HWNs and its QoS routing. The evaluation results show the impact of different network parameters on the performance of QoS-aware routing in HWNs.
Keywords: QoS-aware routing algorithm; Emerging heterogeneous wireless networks; Policy-based QoS supporting system infrastructure; Wireless mobile networks